Seasonal occurrence and vertical distribution of larval and juvenile northern smoothtongue, Leuroglossus schmidti (Pisces, Bathylagidae), in the western subarctic Pacific. (24th September 2020) - Kitamura, Minoru; Murata, Naofumi
Abstract: We investigated the seasonal occurrence and vertical distribution/migration of larval and juvenile northern smoothtongue, Leuroglossus schmidti (Pisces, Bathylagidae), in oceanic areas of the western subarctic Pacific. This species was the most abundant larval fish and one of the most abundant juvenile/adult fish at the study site. Larval recruitment of this species occurred in early March to mid-October. Larvae were found, however, throughout all seasons, suggesting that some had overwintered. The highest abundance (5.8 individuals m –2 ) of larvae was in summer. During summer and autumn, hatching mainly occurred at 100–150-m depth and larvae migrated toward the surface with growth. Once larvae reached about 20 mm in length, they moved below 100 m, and larger larvae (over 24 mm) exhibited diel vertical migration. The abundance of juveniles integrated through the water column was relatively constant (0.3 individuals m –2 ) throughout the study period. They were collected from below 300 m during the day, and part of the population (13–38%) swam into the epipelagic layer at night. The information on early stages of L. schmidti presented here provides a basis for future investigations of mesopelagic fish ecology in oceanic areas of the western subarctic North Pacific Ocean.